AKAL DAN WAHYU DALAM ILMU EKONOMI ISLAM - Neli Neli (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
There are at least two different ways of looking at the relationship between reason and revelation. First, in secular reasoning, the two are separated (dichotomy) so that they are in a confrontational position that cannot be reconciled. Meanwhile, as a revealed religion, Islam accepts both as a source of knowledge. Intellect is an inner element when it comes to revelation. By using the ideas of Max Weber (1864-1920) who suggested that the emergence of economic rationalism was the result of 16th century Protestantism and became the main root of capitalism, but in its development this religious ethical rationality faded and became instrumental rationality (Zweckrationalitat). This is different from Islamic economic rationalism which can be categorized in value-oriented rationality (Wertrationalitat), because considerations of utility, efficiency, profit and so on are not merely priorities but are based on a commitment to values ​​derived from the Qur'an. and Sunnah, both in economic activity and in the analysis of Islamic economics.